Adsorption‐induced Symmetry Distortions in W@Au12 Nanoclusters, Leading to Enhanced Hyperpolarizabilities. Issue 11 (20th October 2016) - Elgavi Sinai, Hadassah; Avnir, David
Abstract: We study how the adsorption of molecules on the stable gold icosahedral W@Au12 nanocluster affects its structure, specifically the inversion symmetry, in relation to the hyperpolarizability of the cluster‐molecule complex. As adsorbed molecules, we selected the achiral physisorbed H2 S and chemisorbed HS radical, the chiral physisorbed cysteine and the chemisorbed cysteine radical. We show that adsorption leads to deformation of W@Au12 that removes the inversion symmetry of the cluster itself. Employing the continuous symmetry measure (CSM) methodology we are able to quantify the distortions, relative to the undisturbed cluster. We then evaluate the hyperpolarizabilities which emerge due to the lack of centrosymmetry. We find that large hyperpolarizabilities, by far exceeding those of the organic molecules, emerge as a result of the complexation of these two different species. This result is of relevance to studies of nonlinear optics, where methods of enhancing that property in molecules of choice are desired. Abstract :